Floating-dislocated elbow in adults: Case reports and literature review. Issue 39 (30th September 2022) - Veliceasa, Bogdan; Pertea, Mihaela; Popescu, Dragos; Carp, Claudiu Adrian; Pinzaru, Roxana; Huzum, Bogdan; Alexa, Ovidiu; Strobescu-Ciobanu, Cristina; Filip, Alexandru
Abstract : Rationale: Floating-dislocated elbow is a severe and extremely rare injury in adults. Reviewing the literature, we found around 6 case reports regarding floating-dislocated elbow in adults. Patient concerns and diagnoses: We report 2 cases of this unusual injury association. Both patients suffered a high energy trauma – fall from a height. Initial X-rays (radiography) revealed in both cases the fractures above and below the elbow (floating elbow) and associated elbow dislocation (floating-dislocated elbow). One case was a type IIIB Gustilo-Anderson open fracture-dislocation with an intra-articular component (olecranon fracture). Interventions and outcomes: Each case had his own management problem regarding what to treat first: the dislocation or the associated fractures? Fractures were treated surgically by reduction and internal fixation, and after elbow dislocation reduction, the upper limb was immobilized in a long, well-padded plaster, with the elbow in 90° of flexion, for 3 weeks. Bone union was observed radiographically at 2 months after surgery in both cases. At the 2-year follow-up we recorded full upper limb recovery in terms of muscular trophism and elbow full range of motion. Lessons: In addition to adding 2 new cases to a lower number of such lesion associations in adults, we also added a new variant of floating-dislocated elbow which has not been reported until now in the literature. Prompt management of these injuries, with stable fixation of the fractures allowed for early rehabilitation with excellent 2-years functional outcome.